Computed Tomographic Diagnosis of Traumatic Atlanto-occipital Rotatory Luxation and Successful Closed Reduction in a Dog - Lye, Gordon; Mathis, Karl; Hill, Sarah; Cattin, Ryan; Hartman, Angela (VCOT Open, 2020)
A 12-year-old, female spayed crossbred dog was presented for traumatic injuries sustained after being hit by a car. The dog was non-ambulatory with a right-sided head tilt on presentation, neurological deficits and signs of external trauma centred on the head. A trauma computed tomography was performed which revealed an atlanto-occipital luxation with narrowing of the vertebral canal. This was treated successfully via closed reduction and confirmed with a repeat computed tomography scan. The dog recovered well following the atlanto-occipital luxation reduction, and was ambulatory the day after the reduction, and neurological signs resolved within 2 days.
Keywords: atlanto-occipital luxation; dog; cervical vertebrae trauma; closed reduction